Vitamin D status in pregnant female and its effect on the maternal and fetal outcome - Seth, Princee; Gehlot, Hanslata; Ghasal, Sarita; Verma, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Vitamin D deficiency is a global public health problem and is very common in pregnancy. Vitamin D status during pregnancy is of very much importance as it’s deficiency leads to increase risk of maternal and fetal complications like hypertensive disorders of pregnancy (HDOP), gestational diabetes mellitus (GDM), preterm, prelabor rupture of membranes (PROM), caesarean section, low birth weight (LBW) babies, intrauterine growth restriction (IUGR), still birth and neonatal intensive care unit (NICU) admission. Methods: 300 pregnant women were studied to assess serum vitamin D level over period of 9 months followed by analytical study done regarding maternal and fetal outcome. Results: Study shows 250 pregnant women out of 300 were deficient in vitamin D. Most of vitamin D deficient patients were under age of 30 years, housewives from rural sector. In both groups, most of patients underwent vaginal delivery. Pregnancies with complication were more seen in vitamin D deficient patients which include higher rate of GDM and HDOP. But other pregnancy complications like preterm, abruption, and prolonged labor were not prominently associated with vitamin D deficiency. Fetal complications and higher NICU admission rate were more seen in babies of vitamin D deficient mothers but no or little effect found on birth weight. Conclusions: Our study has observed higher rate of vitamin D deficiency in pregnant women and its level had significant effect on maternal and fetal complications. Though routine screening is not beneficial attributed to its high prevalence rate and cost effectiveness but since supplementation of vitamin D is simple with low likelihood of toxicity, we recommend adequate exposure to sunlight and supplementation of vitamin D in all pregnant women to keep serum level of 25(OH)D in the normal range for adult >30 ng/ml.